Holocene vegetational and climatic history of the Xuguo Co catchment in the central Tibetan Plateau - Shen, Caiming; Liu, Kam-biu; Tang, Lingyu; Peng, Jinlan (Frontiers in Earth Science, 2023)
A 101-cm core was taken from a large lake in central Tibetan Plateau. Its pollen and loss-on-ignition analyses provide a Holocene vegetational, climatic and environmental history of coring lake catchment. Pollen analysis shows that dense steppe dominated regional vegetation in the early Holocene (9200-8000 cal. yr BP); regional vegetation coverage gradually decreased in the middle Holocene (8000-4100 cal. yr BP); marsh meadow grew in lake edge and sparse steppe occupied the lake catchment after 4100 cal. yr BP. Our result also reveals that 9200-8000 cal. yr BP witnessed summer temperature, monsoonal rainfall, and lake-level maxima, as well as few winter and spring aeolian activities and frequent wildfires; 8000- 4100 cal. yr BP saw a nonlinear decline in temperature, rainfall, lake-level, and wildfire; and modern climatic and environmental conditions were established after 4100 cal. yr BP. Three major monsoon weakening events at ca. 6700, 5800 and 4100 cal. yr BP were detected by pollen signals and proxies of climate and environment.